Single-atom platinum confined by the interlayer nanospace of carbon nitride for efficient photocatalytic hydrogen evolution. (March 2020) - Zeng, Zhenxing; Su, Yan; Quan, Xie; Choi, Wonyong; Zhang, Guanghui; Liu, Ning; Kim, Bupmo; Chen, Shuo; Yu, Hongtao; Zhang, Shushen
Abstract: The fabrication of single atom photocatalyst with high metal atom loading content is essential to achieve high catalytic performance but still remains a big challenge. Herein, we demonstrate a two dimensional confinement strategy to realize the construction of platinum single atom photocatalyst with ultrahigh loading content (8.7 wt%), by using the interlayer subnanospace of layered carbon nitride to confine Pt atoms. To the best of our knowledge, this should be the first example of using the interlayer subnanospace of layered polymeric material to access single atom catalyst with high loading content. We found that the photocatalytic performance is very sensitive to the Pt atom location, being located either at the surface layer or confined by the inner layers. Both theoretical calculation and experimental results show that the interlayer interactions could prominently alter the electronic structures and hence delocalize the charge density of the confined Pt atom to promote proton adsorption, substantially reducing the hydrogen evolution reaction energy barrier. As a result, the as-prepared Pt single atom photocatalyst exhibits highly efficient photocatalytic H2 evolution performance at a rate of 22650 μmol g −1  h −1 with apparent quantum yield (AQY) reaches 22.5% at 420 nm, higher than most polymeric materials. The work demonstrated here offers a new-sight for designing and constructing efficient single atom catalysts for energy and environment-related applications. Graphical abstract: Ultrahigh single Pt atom loading content (8.7 wt%) is achieved by using the interlayer subnanometer space to confine the metal atoms, where the adjacent layers serve as fences to stabilize the metal atoms. The well interlayer environment is found to delocalize the charge density of Pt atom, promoting proton adsorption and reducing the H2 evolution reaction energy barrier, significantly improving the catalytic performance. Image 1 Highlights: Single Pt atom with ultrahigh loading content is fabricated by using the interlayer region of carbon nitride. Confined interlayer environment enables the delocalization of Pt charge density to reduce the HER reaction energy barrier. Pt atoms confined by the interlayer space is more active for HER reaction than the one located at surface layer. SA-Pt/g-C3 N4 -8.7 exhibits excellent photocatalytic H2  evolution performance at a rate of 22650 μmol g −1  h −1 .